Analisis Nilai Ekspor Kopi Provinsi Bali dan Faktor-faktor yang Mempengaruhinya - DASI, SAUMIA KRISNA DEVI; SUDARMA, I MADE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.2, April 2014, 2018)
Analysis of Coffee Export Value of Bali Province and Its Affecting Factors This research aims to find out how much the contribution of coffee exports to the GDP of the agricultural sector of Bali Province, to know the factors that affect the value of coffee exports of Bali Province and to know the trend and the trend forecast of coffee export value for the next five years. This research was conducted in Bali Province using secondary data derived from government agencies. Data were analyzed based on contributions theory, multiple linear regression analysis and trend analysis. The results showed that the average contribution of coffee export of Bali Province to GDP of agriculture of Bali Province is 17,41%. The result of factors that estimated in this research stated that all significant factor to coffee export value of Bali Province is 72,3% and the remaining 27,7% is explained by other factors outside the study. Factors that partially significantly affect the value of coffee exports are coffee export volume of Bali province, world coffee price and US dollar exchange rate. Trend and forecasting export value of Bali Province coffee is projected to increased in the next five years, which is 2016 to 2020. Suggestions that can be given is increaseing export volume is very important to do because the export volume is the most influental factor on export coffee value, so it needs to be done product quality improvement and network marketing expansion.